1988
DOI: 10.1088/0953-4075/21/4/003
|View full text |Cite
|
Sign up to set email alerts
|

New measurements of the cross sections of doubly excited resonances in calcium

Abstract: We report new cross section measurements, believed to be the first involving synchrotron radition together with a 'hot-wire' diode detector, in which we have observed the doubly excited series of C a I at a much improved signal to noise ratio using the radiation from the DORIS I I electron accelerator and the H 4 S Y L 4 B facilities. The data provide " e n information on the 'vanishing width' effect in Ca I and are compared with several calculations of the cross section reported in recent literature. The best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
4
33
1
Order By: Relevance
“…4, where they are seem to be in excellent agreement with the available experimental results [11]. This gives confidence that, using exactly the same theoretical methodology, our calculations should also be reliable for U 0 > 0.…”
Section: B Evolution Of the Photoionization Cross Section With Incresupporting
confidence: 88%
See 1 more Smart Citation
“…4, where they are seem to be in excellent agreement with the available experimental results [11]. This gives confidence that, using exactly the same theoretical methodology, our calculations should also be reliable for U 0 > 0.…”
Section: B Evolution Of the Photoionization Cross Section With Incresupporting
confidence: 88%
“…The photoionization of the outer shell of neutral calcium has been studied using different methods in the past [6][7][8], and experimental data exist [9][10][11]. Three-state R-matrix calculations were found to be quite successful in describing the complex resonance structure endemic in outer-shell photoionization of free Ca [6]; thus, the R-matrix method was selected to perform the calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For such large basis sets the solution of the linear eigensystem (5) at many energies can become time consuming, and for this reason a much more efficient "streamlined" solution method of Greene (12) and 0 0 (13) This partitioning breaks Eq. (5) into two coupled matrix equations, I ccZc+ PCOZ0 (14) r"Z'+ r-Z'=be-Z' (15) Using (14) to eliminate Z' from (15) leads to a matrix equation of much smaller dimension for Z', specifically [I oo I oc(l cc) -Il co]Zo gAooZo (16) …”
Section: Eigenchannel R-matrix Calculation In J J-couplingmentioning
confidence: 99%
“…Accounting for detailed spectroscopy of these heavy atoms, much of it only recently acquired [16],is a second major goal of this paper. Theoretical results are shown to adequately describe photoionization spectra of groundstate strontium and also of the ground state and an excited state of barium.…”
Section: Introductionmentioning
confidence: 99%
“…By employing intermediate resonances, such as the 4s4p 1 P o state, experimentalists control the Ca · ion isotopes that are trapped [22,23,18]. We have recently demonstrated that the use of model potentials gives photoionization cross sections [20] in very good agreement with experiment [24] and the best other theoretical calculations [25]. In figure 3, we build on this work by presenting photoionization cross sections for the m 0 level of the 4s4p 1 P o state, which is used as an intermediate state in the trap loading experiments.…”
Section: Extension To Other Two-electron Systemsmentioning
confidence: 92%